Mechanisms of remarkable wear reduction and evolutions of subsurface microstructure and nano-mechanical properties during dry sliding of nano-grained Ti6Al4V alloy: A comparative study. (May 2022) - Deng, Guanyu; Chong, Yan; Su, Lihong; Zhan, Lihua; Wei, Peitang; Zhao, Xing; Zhang, Liang; Tian, Yanzhong; Zhu, Hongtao; Tsuji, Nobuhiro
Abstract: A comprehensive investigation into dry sliding wear and associated evolutions of subsurface microstructure and nano-mechanical properties of a bulk nano-grained Ti6Al4V alloy (NG-Ti6Al4V) was conducted. Comparing with its coarse-grained counterpart (CG-Ti6Al4V), NG-Ti6Al4V always exhibited lower friction coefficient and greater wear resistance in a wide range of tribological conditions. It was also found that the sliding wear induced nano-mechanical properties and microstructure evolutions in Ti6Al4V alloy were largely dependent on its initial microstructural features. For the first time, TEM observations provided a direct experimental evidence that the originally saturated nanostructure in NG-Ti6Al4V could be further refined by sliding wear. This study proposed an effective strategy to improve the load-bearing ability of Ti6Al4V alloy by producing bulk homogeneous nanostructure. Highlights: NG-Ti6 Al4 V always exhibited better friction and wear performances than CG-Ti6Al4V. Worn surface morphology revealed strong dependence of wear mechanism on load and velocity in two Ti6Al4V materials. Saturated nanograins in NG-Ti6Al4V obtained by HPT process can be further refined by subsequent dry sliding wear. Worn subsurface cross-sectional microstructural features are different between NG-Ti6Al4V and CG-Ti6Al4V.